(untitled) (Applied Biological Research, 2023)
Whiteleg shrimp (Litopenaeus vannamei Boone, 1931) being specific pathogen-free and specific pathogen-resistant fast growing less aggressive species is becoming the choice of farmers for culture. The length-weight relationship helps to explain the stocks; and comparative growth studies are recorded for culture management purposes. In present study, 1200 individuals of Pacific shrimp (L. vannamei) were investigated for length weight relationship (LWR) and condition factor (K). The specimens were randomly collected during January to March 2020 from Dhanlaxmi Aqua Farm, Palsana, Valsad district, Gujarat (India). The length-frequency distribution showed that length group 12.00-14.00 cm was dominant with 447 specimens followed by 14.00-16.00 cm (445), 10.00-12.00 cm (183), 14.00-16.00 cm (101), 8.00-10.00 cm (21) and 18.00-20.00 cm (3). The correlation coefficient (r2) 0.854, intercept (a) -1.994, regression coefficient (b) 2.897 and regression coefficient or growth constant (b) 2.897 (< 3.000) indicated negative allometric growth of white leg shrimp. The values of K obtained were ≤ 1.0 and suggested good and normal growth of shrimp indicating the better adoption of farmmanagement practices during the culture period. These findings may be useful for shrimfarm managers to have better operational activities and assess the health and habitat conditions of rearing shrimps.